Redefining the boundaries of firms: Insights from the corporate social responsibility of the digital platform-based firms and stock returns - KIM, Moo Kung (Institutional Knowledge at Singapore Management University, 2023)
By using a novel dataset, platform firms (those that operate on apps and the internet as their main vector of operations), this study explores the boundaries of the firm through the lens of corporate social responsibility. By examining the CSR scandals of platform-based firms, the paper aims to answer: ‘How do digital platform firms affect the society and capital market and understand the welfare of stakeholders?’. To disentangle the debates in the literature, the study articulates the new framework of the boundaries and scope of firms by proposing broader stakeholders of firms. This research attempts to elucidate the boundaries of the newly formed platform-based firms by revisiting their stakeholders using an event study method with CSR scandals and its reactions from the stock market. The findings of the study suggest that consistent with market efficient hypothesis, the stock market accurately captures unanticipated corporate events. Nevertheless, the results show the significant negative effects of CSR scandals of the platform firms on market reactions, while the ESG ratings of the firms with scandals do not change significantly after the events nor have an effect on market reactions. Furthermore, the results with controlling variables show the changes of ESG ratings have no effect on abnormal returns after several robustness tests of the samples were used in this study. This study provides ample evidence that the stakeholders of platform firms are not well recognized nor incorporated in CSR performance (the ESG ratings) of the firm; hence, it is not conveyed to the investors. Finally, the main contribution of the study is in providing a framework of stakeholder theory by bringing together the discussions for the need for revisiting and refining of the boundaries and scope of the tech-driven digital platform firms through clarifying the doubts about its stakeholders.